Makna ''Adab'' dalam Perspektif Pendidikan Islam - Husaini, Adian (Ta'dibuna: Jurnal Pendidikan Islam, 2018)
"Adab" is one of the Islamic basic vocabularies. According to Prof. Naquib al-Attas, "Adab is recognition and acknowledgement of the reality that knowledge und being are ordered hierarchically according to their various grades and degrees of rank, and of one's proper place in relation to that reality and one's physical, intellectual and spiritual capacities and potentials." There are many hadits of Prophet Muhammad (p.b.u.h.) citing about the significance of adab in Muslim life. Some ulamas also has written so many books on adab. It is a remarkable one, that term "adab" was formulated in the second principle of Pancasila, i.e. "Kemanusiaan yang adil dan beradab." Therefore, the true meaning of adab is must be traced on the framework of the world view of Islam. The meaning of"Adab" as "sopan santun" for instance is not the correct one. This article elaborate the etimological, historical, and technical aspect of the meaning of adab, as cited in Pancasila in light of the purpose of Islamic education.